2005
DOI: 10.1007/s11104-005-5086-y
|View full text |Cite
|
Sign up to set email alerts
|

Plant Colonizers Shape Early N-dynamics in Gopher-mounds

Abstract: Disturbances by fossorial mammals are extremely common in many ecosystems, including the California annual grassland. We compared the impact of juveniles of four common plant colonizers (Aegilops triuncialis, Cerastium glomeratum, Aphanes occidentalis and Lupinus bicolor) on the pools and fluxes of N in mounds created by pocket gophers (Thomomys bottae Mewa). The mechanisms and magnitude of biotic N retention differed among plant species. In mounds colonized by Cerastium, Aphanes and Lupinus, the microbial N p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…The high N:P ratio indicated that L. argenteus probably was limited by availability of P. This finding is consistent with nutrient limitation studies conducted with other species of Lupinus, all of which indicate that atmospheric fixation provides adequate N (Lee et al, 2003;Myrold and Huss-Danell, 2003;Canals et al, 2005) and some of which further suggest that P limits the rate of N-fixation (Crews, 1993;Vitousek, 1999).…”
Section: Speciessupporting
confidence: 85%
“…The high N:P ratio indicated that L. argenteus probably was limited by availability of P. This finding is consistent with nutrient limitation studies conducted with other species of Lupinus, all of which indicate that atmospheric fixation provides adequate N (Lee et al, 2003;Myrold and Huss-Danell, 2003;Canals et al, 2005) and some of which further suggest that P limits the rate of N-fixation (Crews, 1993;Vitousek, 1999).…”
Section: Speciessupporting
confidence: 85%
“…Plant functional diversity effects, in addition to environmental effects, were observed on MBN, DON, total N, urease and phosphatase, and nitrification potential (Table 3 and Figure 4). Several studies investigated the role of vegetation composition in soil microbial N and C. Some detected no change in MBN and MBC with functional group diversity [22,92], while others suggest that PFT and particularly legumes with their important effect on total nitrogen play a great role in shaping soil microbial communities [93,94]. We found that the interaction between grasses and forbs enhanced MBN and phosphatase activity, but PFT diversity had no effect on MBC (Table 3).…”
Section: Plant Functional Diversity Effects On Soil Activity and Fertilitymentioning
confidence: 66%
“…For instance, geophytes are frequently associated with mounds at the local scale and show overlapping distribution with cururos at the biogeographical scale (Contreras et al 1987). Canals et al (2005) showed that the identity of plant species that initially colonize gopher mounds can significantly alter N-dynamics, so F. capreolata could negatively affect native geophytes via changes in nutrient availability. Future studies on this coastal matorral should address the impact of F. capreolata on native plants both beneath shrubs and on cururo mounds in open areas.…”
Section: Discussionmentioning
confidence: 99%